Quality of life measurement in occupational skin diseases. Position paper of the European Academy of Dermatology and Venereology Task Forces on Quality of Life and Patient Oriented Outcomes and Occupational Skin Disease. (13th July 2020) - Chernyshov, P.V.; John, S.M.; Tomas‐Aragones, L.; Gonçalo, M.; Svensson, A.; Bewley, A.; Evers, A.W.M.; Szepietowski, J.C.; Marron, S.E.; Manolache, L.; Pustisek, N.; Suru, A.; et al.
Abstract: The European Academy of Dermatology and Venereology (EADV) has started the 'Healthy Skin @ Work' campaign aimed to raise awareness among the public and EU authorities on the frequency and impact of occupational skin diseases (OSDs). The EADV Task Forces (TFs) on Quality of Life and Patient Oriented Outcomes (QoL/PO) and on OSD present their mutual position statement on QoL assessment in OSDs. The EADV TFs recommend the use of the DLQI as a dermatology‐specific instrument and SF‐36 as a generic instrument in health‐related (HR) QoL studies on OSDs. The OSD‐specific questionnaire, LIOD, is not recommended for general use in its present form because of its three months recall period. The EADV TFs discourage the use of non‐validated and of non‐validated modifications of previously validated HRQoL instruments. The EADV TFs wish to encourage research into: the HRQoL impact of OSDs other than occupational contact dermatitis and hand eczema; comparisons between the effects of different treatments and other interventions on HRQoL in OSDs; and into the HRQoL impairment of patients with OSDs from different countries, and with different provoking factors, to predict if the results of successful therapeutic and educational interventions may be generalized across countries and between occupations.